Effects of dietary methylmercury on the dopaminergic system of adult fathead minnows and their offspring. (28th October 2016) - Bridges, Kristin; Venables, Barney; Roberts, Aaron
Abstract: Mercury (Hg) is a ubiquitous environmental contaminant and potent neurotoxin, which may be transformed by bacteria in aquatic ecosystems to methylmercury (MeHg), an organic form which bioaccumulates and biomagnifies. Consequently, long‐lived organisms at the top of the food web are at risk of dietary MeHg exposure, which can be actively transferred from mother to offspring. Exposure during neurodevelopment can lead to serious, irreversible neurological dysfunction, associated with a variety of cognitive and motor abnormalities. At low dietary concentrations, MeHg exposure has been associated with deficits in attention and hyperactivity in multiple species. Pathways associated with cognitive function and motor activity are primarily associated with the dopaminergic system. The present study used a model fish species, Pimephales promelas, to examine the effects of MeHg exposure on dopamine concentrations and monoamine oxidase activity in embryos and adult brains. Adult fatheads were exposed for 30 d to either a control or a treated diet (0.72 ppm Hg). Embryonic and larval exposures were a result of maternal transfer of dietary MeHg. The authors confirmed hyperactive behaviors in embryos and detected significant changes in embryonic dopamine concentrations. Similar effects on dopamine concentrations were seen in the telencephalon of adult brains. Exposure to MeHg also corresponded with a significant decrease in monoamine oxidase activity in both embryos and brain tissue. Collectively, these results suggest that current exposure scenarios in North America are sufficient to induce alterations to this highly conserved neurochemical pathway in offspring, which may have adverse effects on fish behavior and cognition. Environ Toxicol Chem 2017;36:1077–1084. © 2016 SETAC